Pengaruh Pendapatan Terhadap Pola Konsumsi Mahasiswa Persefektif Maqasid Syariah - Hendarsah Nioo; Khoirul Ibad (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2026)
This study aims to explore the effect of income on the consumption patterns of al-ittihad cianjur students from the maqashid sharia perspective. The development of an increasingly modern era has changed the pattern of human consumption from fulfilling needs to consumptive behavior. Keynes' theory shows that income plays an important role in determining a person's consumption pattern, where humans tend to prioritize primary needs before fulfilling secondary and tertiary needs. In the study of Islamic economics, consumption is not only aimed at obtaining satisfaction, but also paying more attention to human welfare in accordance with the Sharia, namely avoiding behavior that leads to wastefulness and miserliness in consumption. Students, as a group that is experiencing a transition towards financial independence, are often affected by differences in income in meeting basic needs and lifestyle. The methodology used is a quantitative approach with simple linear regression analysis using the SPSS application. The results of the simple linear regression analysis obtained the equation Y = 13.981 + 0.371X, which shows that the income variable has a significant effect on the consumption patterns of STAI Al-Ittihad Cianjur students. The results of the hypothesis test show a calculated t value of 3.772 with a significance value of 0.000 (<0.05), so H? is rejected and H? is accepted.